A randomised in situ trial, measuring the anti‐erosive properties of a stannous‐containing sodium fluoride dentifrice compared with a sodium fluoride/potassium nitrate dentifrice. (March 2014) - Hooper, Susan; Seong, Joon; Macdonald, Emma; Claydon, Nicholas; Hellin, Nicola; Barker, Matthew L.; He, Tao; West, Nicola X.
Abstract : Objectives: To determine if a stabilised, stannous‐containing sodium fluoride dentifrice provides greater enamel protection in situ against intraoral dietary erosive challenges compared with a sodium fluoride/potassium nitrate dentifrice. Methods: A single‐centre, investigator blind, randomised, supervised, two‐treatment, non‐brushing, four‐period crossover in situ study was undertaken, with each test period being 15 days. Thirty‐five healthy adult subjects were recruited to participate in the study, which included four erosive acid challenges per day. Subjects were randomised to product treatment, which included either: (1) a stannous‐containing sodium fluoride dentifrice (Oral‐B ® Pro‐Expert Sensitive) or (2) a sodium fluoride/potassium nitrate dentifrice (Sensodyne ® Pronamel ® ). Each study subject wore an intraoral appliance retaining two sterilised, polished human enamel samples for 6 hours/day. Subjects swished with an allocated dentifrice slurry twice a day and with 250 ml of orange juice for 10 minutes (25 ml/minute over a 10‐minute period) four times per day. The primary and secondary outcomes for this study were enamel loss measured using contact profilometry at days 15 and 5, respectively, using parametric analysis methods. Results: At day 15, a 38% lower enamel loss ( P  < 0.0001) was observed, with estimated medians of 2.03 μm (SE 0.247) and 3.30 μm (SE 0.379), in favour of the stannous‐containing dentifrice. At day 5, specimens treated with the stannous‐containing sodium fluoride dentifrice demonstrated 25% less enamel loss than those treated with the sodium fluoride/potassium nitrate dentifrice. Treatment differences at day 5 were also statistically significant ( P  < 0.05), with estimated medians of 1.37 μm (SE 0.177) and 1.83 μm (SE 0.223), respectively. Conclusions: Results of this in situ study suggest the stabilised, stannous‐containing sodium fluoride dentifrice could be used to provide significantly greater protection to enamel from erosive acid challenge compared with that provided by conventional fluoride‐containing products.